A life worth living : contributions to positive psychology - Csikszentmihalyi, Mihaly; Csikszentmihalyi, Isabella Selega (Series in positive psychology., 2006)
"A Life Worth Living brings together the latest historical, philosophical, and empirical perspectives on what matters for personal happiness and well-being and demonstrates that subjective experience can be studied scientifically and measured accurately."--Jacket